Evaluation of an intervention to promote walking during the commute to work: a cluster randomised controlled trial - Suzanne Audrey; Harriet Fisher; Ashley Cooper; Daisy Gaunt; Kirsty Garfield; Chris Metcalfe; William Hollingworth; Fiona Gillison; Marie Gabe-Walters; Sarah Rodgers; Adrian L. Davis; Philip Insall; et al. (BMC, 2019)
Abstract Background Opportunities for working adults to accumulate recommended physical activity levels (at least 150 min of moderate intensity physical activity in bouts of at least 10 min throughout the week) may include the commute to work. Systematic reviews of interventions to increase active transport suggest studies have tended to be of poor quality, relying on self-report and lacking robust statistical analyses. Methods We conducted a multi-centre parallel-arm cluster randomised controlled trial, in workplaces in south-west England and south Wales, to assess the effectiveness of a behavioural intervention to increase walking during the commute. Workplace-based Walk to Work promoters were trained to implement a 10-week intervention incorporating key behavioural change techniques: providing information; encouraging intention formation; identifying barriers and solutions; goal setting; self-monitoring; providing general encouragement; identifying social support; reviewing goals, and; relapse prevention. Physical activity outcomes were objectively measured using accelerometers and GPS receivers at baseline and 12-month follow-up. The primary outcome was daily minutes of moderate to vigorous physical activity (MVPA). Secondary outcomes included overall levels of physical activity and modal shift (from private car to walking). Cost-consequences analysis included employer, employee and health service costs and outcomes. Results Six hundred fifty-four participants were recruited across 87 workplaces: 10 micro (5-9 employees); 35 small (10-49); 22 medium (50-250); 20 large (250+). The majority of participants lived more than two kilometres from their place of work (89%) and travelled to work by car (65%). At 12-month follow-up, 84 workplaces (41 intervention, 43 control) and 477 employees (73% of those originally recruited) took part in data collection activities. There was no evidence of an intervention effect on MVPA or overall physical activity at 12-month follow-up. The intervention cost on average £181.97 per workplace and £24.19 per participating employee. Conclusions The intervention, focusing primarily on individual behaviour change, was insufficient to change travel behaviour. Our findings contribute to the argument that attention should be directed towards a whole systems approach, focusing on interactions between the correlates of travel behaviour. Trial registration ISRCTN15009100. Prospectively registered. (Date assigned: 10/12/2014).